Outcomes of recurrent stroke in patients with atrial fibrillation according to presumed etiology - Bruno Bacellar Pedreira; Korilyn Sauser Zachrison; Aneesh Singhal; Zhiyu Yan; Jamary Oliveira-Filho; Lee H. Schwamm (Arquivos de Neuro-Psiquiatria)
Background Atrial fibrillation (AF) is a potent risk factor for stroke. The presence of competing etiologies can modify disease outcomes and demand different treatment strategies.